Three-component synthesis of α-indole-β-sulfonyl tetrahydrofurans under metal-free conditions. (12th January 2022) - Xu, Haopeng; Pi, Chao; Wu, Yangjie; Cui, Xiuling
Abstract : An efficient multi-component reaction has been developed for the synthesis of 2, 3-disubstituted tetrahydrofurans in a "one pot" manner, starting from readily available 2-arylindoles, arylsulfonyl azides, and tetrahydrofuran under simple and easily operated reaction conditions. Abstract : An efficient multi-component reaction has been developed for the synthesis of 2, 3-disubstituted tetrahydrofurans in a "one pot" manner, starting from readily available 2-arylindoles, arylsulfonyl azides, and tetrahydrofuran under simple and easily operated reaction conditions. This process provides a wide array of α-indole-β-sulfonyl tetrahydrofurans in good yields with excellent selectivity, avoiding the use of various additives and transition metals as catalysts.